Mini Review: Prostate Cancer Diagnosis and Therapy - Fathurahman, Alfi Taufik; Swasthikawati, Sri; Irawan, Herman; Supriatna, Dadang; Wardiana, Andri (BRIN, 2021)
Cancer, a non-communicable illness, is the leading cause of death worldwide. In 2030, cancer is expected to exceed 21 million cases and 13 million cancer deaths globally. One of the most prevalent and significant types is prostate cancer (PCa). It is commonly associated with adenocarcinoma, which develops from the mucous glands within the organ. This review highlights available detection systems, and therapeutic options in PCa management. One prevention of deadly PCa is early diagnoses, such as prostate-specific antigen (PSA) screening or genomic profiling. Further testing like MRI or CT scan may also be needed to detect cancers that have progressed to other body regions. There are several possible treatments for PCa, including watchful cancer waiting, surgery, radiotherapy, hormone therapy, and chemotherapy. Based on current studies, androgen deprivation therapy (ADT) combined with docetaxel therapy enhanced great results to treat advanced PCa. The latest development, called theranostics, is a single entity that can perform both diagnostic and therapeutic functions. It can detect disease borders, track therapy in real-time, and provide prognostic data. The FDA has already authorized two prostate-specific membrane antigen (PSMA) positron emission tomography (PET) devices: including Gallium 68 PSMA-11 (Ga 68 PSMA-11) and Pylarify (piflufolastat F 18).